Kiwi 'drivers' and 'lookers' : an analysis and examination of the significant contribution of New Zealand Fleet Air Arm Aircrew, of the British Pacific Fleet, to Allied Naval Operations 1944-1945 : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in History at Massey University, Albany, New Zealand - Thomson, Patrick Jeremy Lyon (Massey University, 2012)
This thesis addresses a neglected and under-researched area of New Zealand historiography in World War II: the contribution of New Zealand Fleet Air Arm aircrew serving with the British Pacific Fleet (BPF), from December 1944 to the end of hostilities with Japan in August 1945. The operational experiences, services and sacrifices of these airmen are examined within the wider context of New Zealand’s diplomacy and strategy for the Pacific war. Three research questions are posited. First, what were New Zealand’s different responses to Japanese military aggression in the Pacific, from 1941 to 1944, particularly in association with its allies? Second, what was the genesis of the British Pacific Fleet, and what were its structures and strategic functions? Third, in what ways did New Zealand aircrew contribute to the British Pacific Fleet’s Air Arm operations from 1944 to 1945?
Keywords: New Zealand Fleet Air Arm; British Pacific Fleet; Great Britain Royal Navy Pacific Fleet; Great Britain Royal Navy Fleet Air Arm; Military air pilots; Flight crews; Aircrew; Second World War; World War II; Naval operations; Aerial operations; Pacific Ocean; Japan; New Zealand; World War Two